H2-Optimal Control Synthesis using State Derivative Feedback - Ali, Hazem I. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this paper, the derivation of  optimal control using state derivative feedback to obtain a new control approach is presented. A control approach similar to linear quadratic regulator (LQR) is applied to find the optimal gain matrices that achieve the desired performance. The effectiveness and robustness of the proposed controller can be shown using the uncertain and under-actuated overhead crane system. The results show that the proposed controller can robustly stabilize the system in the presence of system parameters uncertainty. Further, a more desirable time response specifications can be obtained using state derivative feedback  control in comparison to the state feedback  control.